1995
DOI: 10.1002/ajmg.1320550418
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Y chromosome sequences in a 45,X/46,XXq– patient by Southern blot analysis of PCR‐amplified DNA and fluorescent in situ hybridization (FISH)

Abstract: In some cases of gonadal dysgenesis, cytogenetic analysis seems to be discordant with the phenotype of the patients. We have applied techniques such as Southern blot analysis and fluorescent in situ hybridization (FISH) to resolve the phenotype/genotype discrepancy in a patient with ambiguous genitalia in whom the peripheral blood karyotype was 45,X. Gonadectomy at age 7 months showed the gonadal tissue to be prepubertal testis on the left side and a streak gonad on the right. The karyotype obtained from the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 18 publications
(9 reference statements)
2
14
0
Order By: Relevance
“…Five X polymorphic markers were amplified by PCR to determine the parental origin of the single sex chromosome: DMD49 [14], DYS II [15], DXS1283E [16], AR [17]and DXS52 [18]. To detect possible Y hidden mosaicisms, SRY [19], DYZ3 and DYZ1 [20]markers were also amplified by PCR. Internal controls were simultaneously amplified with SRY (DYS II located in Xp), DYZ1 and DYZ3 (IR5, a fragment of 275 bp located in chromosome 19) [21].…”
Section: Methodsmentioning
confidence: 99%
“…Five X polymorphic markers were amplified by PCR to determine the parental origin of the single sex chromosome: DMD49 [14], DYS II [15], DXS1283E [16], AR [17]and DXS52 [18]. To detect possible Y hidden mosaicisms, SRY [19], DYZ3 and DYZ1 [20]markers were also amplified by PCR. Internal controls were simultaneously amplified with SRY (DYS II located in Xp), DYZ1 and DYZ3 (IR5, a fragment of 275 bp located in chromosome 19) [21].…”
Section: Methodsmentioning
confidence: 99%
“…Most marker chromosomes remained unidentified until the advent of fluorescence in situ hybridization (FISH). Molecular analysis has revealed both X-derived and Y-derived markers [Kocova et al, 1995;Schwartz et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetic analysis may fail to detect rare cells bearing a normal or structurally abnormal Y chromosome due to low-level mosaicism or particular tissue distributions [Ostrer and Clayton, 1989;Bisat et al, 1993;Kocova et al, 1995]. Detection of mosaicism depends on several factors, including 1) the number of cells examined [Hook, 1977], 2) the number and type of tissues examined, 3) culture techniques used, and 4) in vivo or in vitro selection against one of the cell lines [Procter et al, 1984].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This way, the application of molecular techniques substantially improves the detection of low-frequency cell lines. Here we present the results of hidden mosaicism on 192 women diagnosed as TS and we focus on the molecular study of the Y chromosome, since numerous studies have shown that 4-20% of Turner women present a Y-chromosome (Kocova et al, 1995), increasing the risk of developing gonadoblastoma (Coto et al, 1995). Although the identity of the gene (or genes) linked to gonadoblastoma has not been established yet, there is evidence indicating that these genes are located near the centromere of the Y chromosome (Salo et al, 1995;Tsuchiya et al, 1995).…”
Section: Introductionmentioning
confidence: 99%